2003
DOI: 10.1083/jcb.200304132
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolin expressed at the cell surface is a marker of endothelial cells in angiogenic blood vessels

Abstract: A tumor-homing peptide, F3, selectively binds to endothelial cells in tumor blood vessels and to tumor cells. Here, we show that the cell surface molecule recognized by F3 is nucleolin. Nucleolin specifically bound to an F3 peptide affinity matrix from extracts of cultured breast carcinoma cells. Antibodies and cell surface biotin labeling revealed nucleolin at the surface of actively growing cells, and these cells bound and internalized fluorescein-conjugated F3 peptide, transporting it into the nucleus. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
422
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(434 citation statements)
references
References 35 publications
10
422
0
2
Order By: Relevance
“…Nucleolin was initially described as a nucleolar protein participating in the transcriptional control of ribosomal RNA genes, in ribosomes maturation and assembly, and in the nucleocytoplasmic transport of ribosomal components [40,41]. It has also been shown that nucleolin can translocate to the plasma membrane in some specific cell types such as endothelial cells and many transformed cells [42]. When present at the cell surface, it has been shown that nucleolin can interact with Erb B receptors or serves as a receptor for L-selectin, midkine and, most interestingly, endostatin [43], a potent antiangiogenic fragment of collagen XVIII.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleolin was initially described as a nucleolar protein participating in the transcriptional control of ribosomal RNA genes, in ribosomes maturation and assembly, and in the nucleocytoplasmic transport of ribosomal components [40,41]. It has also been shown that nucleolin can translocate to the plasma membrane in some specific cell types such as endothelial cells and many transformed cells [42]. When present at the cell surface, it has been shown that nucleolin can interact with Erb B receptors or serves as a receptor for L-selectin, midkine and, most interestingly, endostatin [43], a potent antiangiogenic fragment of collagen XVIII.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleolin has critical and fundamental effects on cell proliferation including organization of nucleolar chromatin, packaging of pre-RNA, rDNA transcription, and ribosome assembly (84)(85)(86). Interestingly, in angiogenic conditions, nucleolin can be mobilized from nucleus to cell surface of endothelium, which is considered as a marker for angiogenic vasculature (87,88). Compared with other reported receptors, cell surface nucleolin has a tissue specific distribution and is only expressed on angiogenic blood vessels but not mature ones.…”
Section: Signaling Pathwaysmentioning
confidence: 99%
“…Nucleolin is modified by ADP-ribosylation, 117 but the some tumor cells. 91 Although these ligands can impair nucleolin binding to target mRNAs, it is not yet known if their antitumor actions are explained by nucleolin's altered RNA-binding activity.…”
Section: Nucleolin and The Hallmarks Of Cancermentioning
confidence: 99%
“…[88][89][90] Nucleolin was found to be the receptor of endostatin and peptides F3 and N6L. [91][92][93] Besides tumorigenesis, angiogenesis and signaling pathways, cell-surface nucleolin also participates in viral and bacterial infection. For example, HIV inhibitors such as pleiotrophin (PTN), the pseudopeptide HB-19, and the cytokine midkine bind specifically to cell surface-expressed nucleolin and inhibit HIV entry, indicating that nucleolin facilitates viral entry to the host cell.…”
Section: Nucleolin Target Transcriptsmentioning
confidence: 99%